O modelo societário das companhias de exploração colonial portuguesas no século XVIII - Pinto de Albuquerque, Tomás (História do Direito, 2025)
The study examines the evolution of Portuguese colonial exploration companies in the 18th century, highlighting the Companhia Geral do Grão-Pará e Maranhão and the Companhia Geral do Pernambuco e Paraíba. It analyses the legal characteristics that defined these companies, comparing them with European company models such as the VOC and the EIC. Although it recognises the influence of foreign models, it argues that the Portuguese experiences have their own roots, including the introduction of the concept of limited liability and the immobility of capital. The Pombaline companies had the characteristics of public limited companies, allowing for the transfer of shares and the protection of shareholders' rights. However, the limited duration of the companies and their relationship with the Crown brought them closer to regulated companies. Thus, the author concludes that the result of similarities with European models meant that Portuguese companies played a significant role in dynamising the capital market in Portugal in the second half of the 18th century.